Tradisi Pembacaan Ayat-ayat Al-Qur'an: (Kajian Living Qur’an di TPQ Nurussholah Kampung Marhaban Kecamatan Singkawang Selatan Kota Singkawang ) - Faizah, Siti; Rosyidah, Ainur (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
This study discusses the tradition of reading the verses of the Koran at TPQ Nurussholah which was born from communal practices that show the social reception of certain people or communities towards the Koran.In this case, it is TPQ Nurussholah, Marhaban village, South Singkawang district, Singkawang city. All students who are in TPQ are required to take part in readings that are routinely carried out after the maghrib congregation. In the tradition of reading, namely reading the verses of the Koran.Among the verses of the Koran are in the surah Al-Fatihah, Yasin, As-Sajadah, Al-waqi'ah, Al-mulk. This study focuses on the practice of reading the verses of the Koran in TPQ Nurussholah, Kampung Marhaban, Sedau Village and the meaning of the community towards the tradition of reading the verses of the Koran in TPQ Nurussholah, Kampung Marhaban, Sedau Village. This research uses a qualitative descriptive method with an ethnographic approach and the theory of the sociology of knowledge by Karl Mainnhem.The results of the research in this writing are first, the practice of reading verses of the Koran in a tradition carried out routinely and istiqomah after congregation Maghrib prayer and followed by all students except those who are menstruating. Beginning with the reading of the surah alfatihah, the second reading of the verses of the Koran which includes the five surah then ending with a prayer.The tradition of reading these verses of the Koran at the TPQ Musholla Nurussholah when viewed by using the meaning of an action in Karl Mainnhem's sociological theory of knowledge, there are three categories of meaning obtained. The objective meaning is defined, the expressive meaning is a form of learning, fadhilah (virtue), as well as the expressive meaning that shows psychology or peace of mind and the meaning of documentary is as a culture